2020
DOI: 10.1002/cam4.3411
|View full text |Cite
|
Sign up to set email alerts
|

BUB1B promotes hepatocellular carcinoma progression via activation of the mTORC1 signaling pathway

Abstract: Background and Aims Accumulating studies identified that BUB1 mitotic checkpoint serine/threonine kinase B (BUB1B) is integrally involved in the initiation and development of tumors. Nevertheless, the precise biological role and underlying mechanisms of BUB1B in hepatocellular carcinoma (HCC) remain indistinct. Method To figure out the role of BUB1B in HCC, we first assessed its expression using The Cancer Genome Atlas (TCGA) and Gene Expression Profiling Interactive Analysis (GEPIA) databases. We then verifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 37 publications
(72 reference statements)
0
35
0
Order By: Relevance
“…BUB1 promotes the occurrence and development of HCC by activating mTORC1-related proteins (33). PLK1 and CDK1 are important molecules in the abnormal cell cycle of HCC cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…BUB1 promotes the occurrence and development of HCC by activating mTORC1-related proteins (33). PLK1 and CDK1 are important molecules in the abnormal cell cycle of HCC cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation in BUB genes have been reported in many cancers [ 6 , 14 19 , 21 , 23 , 24 ]. However, the role that BUB factors play in sarcoma remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that BUB1 mitotic checkpoint serine/threonine kinase B (BUB1B) could promote the proliferation of prostate cancer [ 46 ]. BUB1B also promotes the progression of hepatocellular carcinoma by activating the mammalian target of the rapamycin complex 1 (mTORC1) signaling pathway [ 47 ]. However, the role and function of BUB1B in the crosstalk between G-SCs/P-SCs and OSCC have been poorly studied.…”
Section: Discussionmentioning
confidence: 99%